Fragility curves for rapid assessment of earthquake-induced damage to earth-retaining walls starting from optimal seismic intensity measures. Issue 152 (January 2022) - Cosentini, Renato Maria; Bozzoni, Francesca
A bstract: The earthquake-induced damage to earth-retaining structures located along roadway network clearly affects the operations during the emergency and rescue phases in the immediate aftermath of a seismic event. The prompt estimation of the seismic vulnerability of a structure or a typological class of structures having a similar seismic behaviour is of foremost importance. In this framework, fragility curves represent an effective tool which can be adopted for quickly evaluating the seismic response of strategic structures. Aim of this study is to propose novel sets of fragility functions for earth-retaining structures, which adopt as input the Intensity Measures (IMs) best correlated to the response of the walls. First, target earth-retaining structures identified along the Italian roadway network are numerically modelled and then two-dimensional (2D) dynamic analyses carried out with reference to different geometrical features of the structure (i.e. height and shape of the walls) and configurations of the backfill. Metrics such as efficiency, practicality, proficiency, and sufficiency are assessed for different demand parameters (overall 35 IMs). The structure response is expressed in terms of horizontal displacement and rotation of the wall. Fragility functions for peak values of velocity (PGV) and acceleration (PGA) are developed. The fragility models are then applied for computing the seismic damage scenario associated to a real earthquake occurred in Central Italy in 2016. Predictive capabilities of the models are assessed by comparing surveyed damages. The proposed tools are useful in emergency management and also during preparedness phase to identify the priority actions and proper countermeasures for seismic risk mitigation. Highlights: 2D dynamic analyses of earth-retaining walls along the Italian roadway network. Identification of the optimal intensity measures. Development of novel fragility curves for earth-retaining walls. Computation of seismic damage scenario associated to a real earthquake.